Using Web-quest technologies in higher schools in the preparation of future experts - Савченко, Лариса Олексіївна (Pedagogy of Higher and Secondary Education, 2017)
The article reveals the concept of «Web-quest technologies and substantiates as didactic structure within which the teacher creates a search activity for students, sets the parameters of this activity and determines its time limits. In this case teachers cease to be» a source of knowledge but create the necessary conditions for finding information, and students are transformed from passive objects of educational activity in its active subjects. Web Quest is an interactive process in which students discover the motives for the independent gain of the required knowledge. To effectively enhance the quality of training students in the classroom in higher pedagogical schools in our opinion, the introduction of Webquest technology is essential. Web quest does not have egough coveradge in modern pedadogical literature. Web Quest is the problem task with elements of role-playing game, for the performance of which the use Internet resources is reqired.